Prosedur dan Jenis Permintaan Visum et Repertum di Rumah Sakit: Literature Review - Dies Puji Ramadhani; Ida Sugiarti (Lembaga Penerbitan Universitas Esa Unggul, 2021)
AbstractVisum et repertum (VeR) is a medical certificate used for judicial needs in the form of a written report made by a doctor containing the results of the examination. VeR is one of the five legal pieces of evidence in court. Making a VeR that is not following hospital procedures can lead to the submission of evidence in court proceedings. This study aims to determine the standard procedure for implementing medical information for VeR and the types of cases for which a VeR is requested. This type of research is a literature review using Google Scholar and Garuda databases with a boolean system strategy. The flow of the implementation of patient medical information for VeR begins with the police submitting a letter of request for VeR to the hospital administration by bringing the requirements of an official request letter from the director of the hospital. The visa request letter and the report are placed in the Medical Record Installation for further processing by the Medical Record. The types of cases requested for VeR are divided into two, namely for living victims and dead victims. Living victims are divided into injuries, sexual crimes, and psychiatric.Keywords: literature review, visum et repertum (VeR), fixed procedure, type of request. AbstrakVisum et repertum (VeR) merupakan surat keterangan medis yang sifatnya dipergunakan untuk kebutuhan peradilan berupa laporan tertulis yang dibuat oleh dokter yang memuat hasil pemeriksaan. Visum et Repertum merupakan salah satu dari lima alat bukti yang sah di pengadilan. Pembuatan visum et repertum yang tidak sesuai dengan prosedur tetap rumah sakit dapat menghambat penyampaian bukti dalam proses pengadilan. Penelitian bertujuan untuk mengetahui prosedur tetap pelaksanaan pelepasan informasi medis untuk keperluan visum et repertum serta jenis permintaan visum et repertum. Jenis penelitian adalah literature review menggunakan database Google Scholar dan Garuda dengan strategi boolean system. Alur pelaksanaan pelepasan informasi medis pasien untuk keperluan visum et repertum dimulai dengan pihak kepolisian menyerahkan surat permintaan visum et repertum ke bagian tata usaha Rumah Sakit dengan membawa persyaratan surat permohonan resmi dari kepolisian kepada direktur Rumah Sakit. Surat permintaan visum et repertum tersebut didisposisikan ke Instalasi Rekam Medis untuk selanjutnya diproses. Jenis kasus yang dimintakan visum et repertum dibagi menjadi dua, yaitu untuk korban hidup dan korban mati. Korban hidup terbagi menjadi perlukaan, kejahatan seksual, dan psikiatrik.Kata Kunci: literature review, visum et repertum, prosedur tetap, jenis permintaan